Rice Galaxy: an open resource for plant science - Juanillas, Venice; DeReeper, Alexis; Beaume, Nicolas; Droc, Gaëtan; Dizon, Joshua; Mendoza, John Robert; Perdon, Jon Peter; Mansueto, Locedie; Triplett, Lindsay; Lang, Jillian; Zhou, Gabriel; Ratharanjan, Kunalan; et al. (Oxford University Press, 2019)
Rice molecular genetics, breeding, genetic diversity, and allied research (such as rice-pathogen interaction) have adopted sequencing technologies and high-density genotyping platforms for genome variation analysis and gene discovery. Germplasm collections representing rice diversity, improved varieties, and elite breeding materials are accessible through rice gene banks for use in research and breeding, with many having genome sequences and high-density genotype data available. Combining phenotypic and genotypic information on these accessions enables genome-wide association analysis, which is driving quantitative trait loci discovery and molecular marker development. Comparative sequence analyses across quantitative trait loci regions facilitate the discovery of novel alleles. Analyses involving DNA sequences and large genotyping matrices for thousands of samples, however, pose a challenge to non−computer savvy rice researchers.